The Use of Self Construction Animation Learning Software to Improve the Students Concept Mastery on Structure and Functions of Plants - Akbar Shidiq I; Diana Rochintaniawati; Yayan Sanjaya (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The use of learning media plays an ultimate role in Biology learning to assist students in the understanding subject matter. This study aims to improve students’ concept mastery after using self-construction animation learning software in a subject matter of structure and function of the plant. The method used in this study was Quasi-Experiment, while the design used was Pretest-Posttest None-equivalent Groups Design Research. The study was conducted in the 8th grade of MTs Ma’arif Cikeruh Jatinangor. The sampling used Purposive Sampling, thus 8th B was chosen as the experimental class while 8th was chosen as the control class. The instrument used in this study was a written test in the form of multiple choices. The taken data were analysed by using N-Gain to discover the improvement of concept mastery and hypothesis test analysis to discover the differences of concept mastery improvement. The result of the study shows that there is a significant difference in the concept mastery improvement in structure and function of plants subject matter. The result of NGain analysis shows that such a media mentioned earlier can improve students’ concept mastery.